O novo marco legal da regularização fundiária urbana: uma análise crítica da Lei nº 13.465/17 - Amorim Sobrinho, João Henrique de (2022)
This paper analyzes the new Reurb’s legal framework, considering the legislative advances and setbacks concerning the matter from a historical context, also enabling the understanding of its institutes and its applicability in the practical field. It critically evaluates the new legal framework and, comparing it to the previous legislation, seeks to provide a glimpse of the damage caused to urban policy engendered in the Constitution of the Republic by virtue of its advent, pointing to the need for a legislative return to the previous scenario. It also provides data on the progress of Reurb processes in the State of São Paulo, within the scope of the Legal City Program